Experiential Learning of Local Relational Tasks for Global Sustainable Development by Using a Behavioral Simulation - Craps, Marc; Brugnach, Marcela (Frontiers in Sustainability, 2021)
The interdependent character of sustainability challenges calls for collaboration among actors with different capabilities, interests and knowledge frames. Behavioral simulations offer good opportunities to learn about dealing with these differences. They are based on an “experiential learning” approach that integrates the direct experience of the participants during a simulation exercise with reflection, theorizing and acting. As such the simulation is able to mobilize the “minds, hearts and hands” of the participants to stimulate not only cognitive, but also affective and moral learning in an embodied way. This is considered of utmost importance in education for sustainable development. The simulation exercise presented in this manuscript is inspired by a real case in the Southern Andes of Ecuador, where an existing multi-actor committee for the co-management of the regional UNESCO Biosphere is challenged by the arrival of an international mining company. The results are based on an analysis of the simulation sessions with three different groups: 1. social and environmental experts that have experience in the context of the case; 2. students in International Business Management; and 3. students in Water Engineering. The participants tap into the potential of individual and group reflection to learn from their own experience. They demonstrate an increased awareness of the importance of the relations between the stakeholders to deal adequately with the wicked nature of the case. The innovation of the tool consists in the possibility to address in a systematic and explicit way the relational tasks that are needed in local contexts to address global sustainability challenges. Especially the attention given to ambidexterity to address the tough tension between collaboration and power plays is rarely covered by other tools..